Deux ou trois choses dont je suis sûre - Allison, Dorothy (Cambourakis, 2020)
Autrice de Peau, recueil d’essais devenu culte, Dorothy Allison a grandi dans le sud des États-Unis, dans un contexte de misère sociale et de violences familiales et sexuelles. Dans Deux ou trois choses dont je suis sûre, elle raconte les femmes de sa famille – mère, sœurs, cousines, filles et tantes –, rendant hommage à leur force, leur humour, leur beauté et surtout leur détermination obstinée face au quotidien qui les accable. Illustré de photographies de sa collection personnelle, ce livre montre à quel point les petites histoires d’une génération peuvent acquérir le statut de légende pour les générations suivantes. Un ouvrage où la vision singulière de Dorothy Allison s’exprime avec beaucoup d’humour et d’émotion
Keywords: 1900-1999; amériques; approches et analyses; histoire et politique; inégalités; mémoire familiale; périodes historiques; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

Save Yourself - Esposito, Cameron (Grand Central Publishing, 2020)
This "hilarious and honest" bestselling memoir from a rising comedy star tackles issues of gender, sexuality, feminism, and the Catholic childhood that prepared her for a career as an outspoken lesbian comedian (Abby Wambach).Cameron Esposito wanted to be a priest and ended up a stand-up comic. Now she would like to tell the whole queer as hell story. Her story. Not the sidebar to a straight person's rebirth-she doesn't give a makeover or plan a wedding or get a couple back together. This isn't a queer tragedy. She doesn't die at the end of this book, having finally decided to kiss the girl. It's the sexy, honest, bumpy, and triumphant dyke's tale her younger, wasn't-allowed-to-watch-Ellen self needed to read. Because there was a long time when she thought she wouldn't make it. Not as a comic, but as a human. SAVE YOURSELF is full of funny and insightful recollections about everything from coming out (at a Catholic college where sexual orientation wasn't in the nondiscrimination policy) to how joining the circus can help you become a better comic (so much nudity) to accepting yourself for who you are-even if you're, say, a bowl cut-sporting, bespectacled, gender-nonconforming child with an eye patch (which Cameron was). Packed with heart, humor, and cringeworthy stories anyone who has gone through puberty, fallen in love, started a career, or had period sex in Rome can relate to, Cameron's memoir is for that timid, fenced-in kid in all of us-and the fearless stand-up yearning to break free.
Keywords: amériques; approches et analyses; corps; humour; identités LGBTQIA2+; personnes lesbiennes; privilèges; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; travail; états-unis

Sex & gender: An introduction - Lips, Hilary M. (Waveland Press, Inc., 2020)
Are sex and gender really two different things? How malleable is gender identity? Do both gender and sex have to be conceptualized as binaries—as having two distinct but complementary categories? Should we emphasize gender differences, or is that the wrong question? When should we call a gender difference “small”? Are women really “nonaggressive” or does that label stem from stereotyping? How does subtle or “modern” sexism work on its targets? Scholarship on these and other gender-related questions has exploded in recent years. Hilary Lips synthesizes that research for students in an accessible and readable way. Concepts on sex and gender are presented with the social context in which they were developed. As in previous editions, Lips takes a multicultural approach, discussing the gender experiences of people from a wide range of races, cultures, socioeconomic statuses, and gender and sexual identities. She emphasizes empirical research but takes a critical approach to that research.
Keywords: analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; construction du savoir; corps; cours; discipline; discours dominant; essentialisation; hétérosexisme; identité; identité sexuelle; inégalités; premier cycle; psy4910; psychologie; santé; sciences humaines; sexe/genre; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; trs3550; études de genres